Risk-based Regulation of Russian Universities: Risk Indicators and Their Use for State Control Purposes - E. A. Ponomareva; A. D. Savina; N. S. Antonenko (Высшее образование в России)
The article is devoted to the identification and analysis of indicators of the risk of low-quality education in Russian universities. In 2021-2022, the approach to higher education inspections has changed significantly: accreditation monitoring has been introduced, it includes eight indicators. However, this monitoring was formed by the expert community, so the results of its testing in practice have yet to be analyzed. The purpose of this work is to identify risk factors for estimation the likelihood of violations of mandatory requirements by universities, and to develop recommendations for expanding the set of risk indicators included in accreditation monitoring. The main methods used in the work are methods of quantitative analysis, including econometric modeling. The novelty of the work is determined by the approach used: risk indicators are identified using a quantitative econometric analysis of data on the observed characteristics and results of inspections of Russian universities in 2015-2019. The results of the study indicate the possibility of supplementing the set of accreditation monitoring indicators. As additional indicators, first of all, various characteristics of research activities of universities can be used. Such a change in accreditation monitoring will increase its effectiveness as a preliminary assessment tool used in the implementation of a risk-based approach to state control. In cases where the assessment of even extended monitoring is ambiguous, the quantitative model proposed by the authors can be used.